Pengaruh Kebijakan Hutang, Keputusan Investasi dan Free Cash Flow Terhadap Nilai Perusahaan - Dini Amalia Rahma; Dian Widiyati (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2024)
This research aims to analyze the influence of debt policy, investment decisions and free cash flow on company value. This research was conducted by analyzing the financial reports of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 period. The sample used in the research was 11 companies or 55 observation data from the transportation and logistics sector listed on the Indonesia Stock Exchange (BEI) during 2018-2022 using quantitative methods with a sampling technique using purposive sampling. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this research are Debt Policy (X1) as the first independent variable, Investment Decision (X2) as the second independent variable, and Free Cash Flow (X3) as the third independent variable and Company Value (Y) as the dependent variable. The panel data regression method was used as the research methodology in this study. Analysis of research results using the EViews 11 Student Version Lite device. The results of this research show that the best model is the Fixed Effect Model (FEM). The results of this research t test (partial) show that Debt Policy partially has no effect on Company Value, Investment Decisions partially have an effect on Company Value